Karakteristik Pasang Surut Laut di Pulau Jawa - H Haryono; Sri Narni (Forum Teknik, 2004)
Sea tides  are  cailsed  by  atlraction  of heavenly  bodies  especially moon and  sun to  the envelope of sea  water  of  lhe  earth.  At different  places  of  the  earth,  sea tides  characteristics  are different.Sea tides  raw data collected from several  sea  tides  stations  in  Java  island  are  processed using sea tides  computer software  and amplitudes of  sea tidal  constants  are determined.  Based on  Formzal formula, Formzal numbers  are  calculated,  and  sea  tides  characteristics  areinterpreted.  Linking  lhe  sea  tides  characteristic infurnntion  to  the  digital  map of Java  island, sea tides  characleristics  map  is  discovered.The  result  of the  research  is  information  on  sea  tides  charateristics for Jova  island. Normally,  mixed  sea  lides  characteristics  are  discovered  in  Java  island.  Many  users,  e.g. hydrographic  surveyors, fishermen, coaslal engineers,  elc.  need  sea  tides  characteristics information for their  works.Keywords: sea  lides,  Formzal  nurnbers,  Java  island.